2023
DOI: 10.1371/journal.pone.0288855
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based violence among healthcare students: Prevalence, description and associated factors

Marie-Pierre Tavolacci,
Alice Karmaly,
Najla El Gharbi-Hamza
et al.

Abstract: Objectives The aims of the current study were 1) to provide the prevalence of five types of gender-based violence (GBV) among male and female healthcare students; 2) to describe perpetrators’ status, where the GBV occurred, and psychological and behavioural impacts of the GBV; and 3) to identify factors associated with GBV. Design A cross-sectional study was conducted among voluntary healthcare students in France. Setting Health Campus at Rouen and nursing schools in Normandy, France. Participants Volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The professional hierarchy among midwives, nurses, physicians, and others [ 13 , 47 , 51 , 83 , 87 , 90 , 96 , 105 , 110 , 134 , 140 , 143 , 159 , 165 , 169 172 , 183 , 189 , 198 , 205 , 224 ] and the organizational hierarchy within or between different professionals [ 47 , 80 , 95 , 116 , 152 , 165 , 184 , 194 , 204 , 226 , 230 , 242 ] was found to contribute to various forms of workplace violence. Some studies reported a higher prevalence of WPV among women across the workforce; they reported that female nurses’ experience of WPV was higher than female physicians in Australia [ 83 ], Brazil [ 96 ], Canary Island [ 189 ], France [ 197 ], Kenya [ 183 ], Italy [ 31 , 105 ], Japan [ 110 ], Turkey [ 138 ], Ghana [ 36 ], and India [ 146 ]. Verbal abuse was prevalent for female nurses in the Caribbean [ 13 ], Norway [ 224 ], and Cyprus [ 231 ] from patients or relatives; aggression ...…”
Section: Resultsmentioning
confidence: 99%
“…The professional hierarchy among midwives, nurses, physicians, and others [ 13 , 47 , 51 , 83 , 87 , 90 , 96 , 105 , 110 , 134 , 140 , 143 , 159 , 165 , 169 172 , 183 , 189 , 198 , 205 , 224 ] and the organizational hierarchy within or between different professionals [ 47 , 80 , 95 , 116 , 152 , 165 , 184 , 194 , 204 , 226 , 230 , 242 ] was found to contribute to various forms of workplace violence. Some studies reported a higher prevalence of WPV among women across the workforce; they reported that female nurses’ experience of WPV was higher than female physicians in Australia [ 83 ], Brazil [ 96 ], Canary Island [ 189 ], France [ 197 ], Kenya [ 183 ], Italy [ 31 , 105 ], Japan [ 110 ], Turkey [ 138 ], Ghana [ 36 ], and India [ 146 ]. Verbal abuse was prevalent for female nurses in the Caribbean [ 13 ], Norway [ 224 ], and Cyprus [ 231 ] from patients or relatives; aggression ...…”
Section: Resultsmentioning
confidence: 99%
“…More than 40% of students have experienced at least one form of GBV since the commencement of their healthcare study. Regardless of the kind of GBV, the perpetrators were other students, healthcare professionals, and patients ( Tavolacci et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%